Body-worn camera videos and public perceptions of police: an experiment on positive video exposure and community-police relations - Saulnier, Alana (Policing and society, 2023)
Objective Explore whether exposure to positive BWC videos – particularly, acts of heroism – affects public perceptions of police while accounting for existing trust in police.Method An online vignette-style experiment was conducted in which participants’ (N = 407; x¯age = 41.94 [s = 12.74]; 51% women, 80% White) existing trust in police was measured before random assignment to either view a short series of positive BWC videos or not. All participants then read a vignette describing a traffic stop. Participants reported their perceptions of procedural and distributive justice as well as perceptions of police more generally.Results Participants with higher existing trust in police reported more positive evaluations across all outcomes measured. Exposure to positive BWC videos only increased reported willingness to cooperate with police. However, trust in police and exposure to BWC videos produced an interaction effect: when participants’ existing trust in police was low, viewing positive BWC videos improved evaluations of officer respect and procedural justice as well as willingness to cooperate with police. Participants with low trust in police who viewed the positive videos became more similar to participants with high existing trust in police.Conclusion The findings indicate that exposure to positive BWC videos can moderate the negative effect of low trust in police. In an applied sense, the results suggest that police-community relations may be enhanced by circulating videos that depict acts of police heroism when such events have occurred and are captured on film.